Field-independence as a characteristic of police officers’ vital activity - D. V. Shvets (Law and Safety)
The professional thinking of police officers is integral to the developed legal consciousness, and its significant components are critical thinking and field-independence. Field-dependence and field-independence are respond through individually unique means of perception, receipt and processing of information, which defines them as typical for the subject ways of solving problems, thinking, perception and memorization. It is mpirically revealed the features of states and personality traits and extraversion/neuroticism in police officers with varying severity of field-dependence/field-independence.